Quantitative analysis of gadolinium doped cerium oxide thin films via online-LASIL-ICP-OES. Issue 11 (17th October 2019) - Herzig, C.; Frank, J.; Opitz, A. K.; Fleig, J.; Limbeck, A.
Abstract : LASIL-ICP-OES is used to determine the stoichiometry of gadolinium doped cerium oxide thin films ranging from 220 to 14 nm with high accuracy and precision. Abstract : Laser ablation of solids in liquid (LASIL) coupled with ICP-OES detection was used as a new sampling technique for the analysis of ceramic thin films. The quantitative analysis of such thin films requires high sensitivity, due to a very low absolute analyte amount. For this purpose, the ablation cell, which is a key element for online coupling of the particle generation and detection system, was improved and the washout times could be reduced by a factor of 6 compared to previous publications. To demonstrate the capabilities of this online-LASIL technique, the elemental compositions of gadolinium doped cerium oxide (GDC) thin films were determined and energy dispersive X-ray microanalysis (SEM-EDX) was used as a reference technique. The film thickness of the investigated samples ranged from 220 nm to 14 nm. While SEM-EDX comes to its limits for films below 110 nm, online-LASIL-ICP-OES shows constant high accuracy and precision for all investigated films.